MOTIVATION AND ITS EFFECTIVENESS IN LANGUAGE LEARNING - Akhmadova Maftunaxon Ibodullo kizi (Bright Mind Publishing, 2025)
Motivation plays a crucial role in language learning, influencing learners' engagement, persistence, and overall success. This paper explores the types of motivation in language acquisition, including intrinsic and extrinsic motivation, and their impact on learners' progress. Furthermore, it examines factors that enhance motivation and discusses strategies to maintain a high level of enthusiasm in language learning.
Keywords: Motivation, language learning, intrinsic motivation, extrinsic motivation, learning strategies, student engagement, educational psychology, gamification, digital tools, autonomous learning.